Digital Skills of Medical Workers as a Staffing Priority in a Healthcare System - L. D. Gurtskoy; E. K. Smirnova; T. V. Baranova; A. S. Tykyl-Ool (Здоровье мегаполиса, 2024)
Introduction. Digital transformation is now integrated into all aspects of modern society around the world, including healthcare. Medical professionals actively use digital services and recommend various wearable devices to patients. The spread of digital technologies requires an appropriate level of digital literacy, which is one of the basic aspects of the professional skills of medical professionals.The purpose of the article was to study theoretical approaches to determining the concept of digital literacy skills of medical professionals based on an analysis of scientific literature.Materials and methods. In this paper, the method of content analysis of scientific publications on the digital literacy of medical professionals was used. The authors studied and analyzed articles published in the PubMed database for the period from 2018 to 2023. The study was based on the definition of “digital literacy of medical workers” as a theoretical construct and object of study in the context of assessing the level of education in applied research.Results. There is a lack of broad research on the self-assessment of digital skills in different groups of medical professionals. It is necessary to obtain broader data on the digital literacy of medical workers in different countries and regions. Places with lower levels of digital literacy require more research in order to better understand the needs for knowledge, skills, and abilities among medical workers.